Le narrateur dans l’image. Analyse comparative d’une photographie de Jeff Wall et d’un texte de Walter Benjamin - Fraser, Marie (RACAR : Revue d'art canadienne / Canadian Art Review, 2004)
This article deals with the problem of text and image in contemporary art, as exemplified in a photograph by Jeff Wall called The Storyteller (1986). This image is analysed, taking as reference Manet’s Déjeuner sur l’herbe as well as Walter Benjamin’s essay of 1936 on the subject of the narrator. The main points in this comparative analysis are the role of the narrator both in text and image, oral tradition versus visual space, the concept of the picture and the tradition of story representation. The author proposes the idea that modernity introduced a major change in the art of storytelling and in the narrative function of image.